Attorney-client privilege in Polish law and legal practice – on legal gaps and some controversial matters - Hryniewicz-Lach, Elżbieta (ERA-Forum, 2023)
This article presents the legal framework of attorney-client privilege in Poland, indicating situations when an attorney is entitled or obliged to reveal information covered, in principle, by professional secrecy, as well as the consequences of an attorney’s erroneous evaluation in this regard. The author refers to provisions which require legal amendment or functional interpretation in order to guarantee respect for attorney-client privilege in legal proceedings, pointing out also controversial interpretations in court practice of what, in principle, are clear legal provisions relating to attorney duties. Finally, the poor perspective for changes in relevant field and the reasons for this are explained.